Teologia pubblica: dall'orizzonte soteriologico all'ordine sociale - Scaramuzzi, Francesco (Rassegna di teologia, 2025)
Public theology is emerging today as one of the most compelling fields in theological discourse. However, like many young disciplines, it faces certain challenges, chief among them being the difficulty of arriving at a clear and shared definition. This study aims to revisit the foundational insight of Martin Marty, credited with coining the term "public theology", and to provide an analysis that elucidates its nature and purpose.